Knowledge translation in Aboriginal and Torres Strait Islander research contexts in Australia: scoping review protocol. Issue 7 (15th July 2022) - Brinckley, Makayla-May; Bourke, Sarah; Watkin Lui, Felecia; Lovett, Raymond
Abstract : Introduction: Knowledge translation (KT) involves bridging the gaps between research knowledge and research application or practice, by sharing this knowledge with knowledge-users. KT is increasingly being used in research with Indigenous peoples globally to address the top-down and inappropriate research approaches commonly used in Indigenous research. Employing KT in Indigenous research in Australia is an emergent field, despite Aboriginal and Torres Strait Islander peoples having conducted KT for generations. There is limited evidence which demonstrates how KT is applied in the Aboriginal/Torres Strait Islander context. Results will benefit researchers by demonstrating ways of appropriately translating research findings to knowledge-users, including Aboriginal and Torres Strait Islander communities, researchers and policy makers. The scoping review will also inform a KT definition, method and practices used in a large-scale, longitudinal cohort study of Aboriginal and Torres Strait Islander adults: the Mayi Kuwayu Study. Methods and analysis: Under guidance of an Aboriginal and Torres Strait Islander governance committee, we will conduct a scoping review on KT in Aboriginal/Torres Strait Islander research. We will follow the scoping review method outlined by the Joanna Briggs Institute. We will search the ANU SuperSearch, and grey and hard to find literature in June 2022. Abstracts and full-text articles will be screened by two independent reviewers. We will include studies that relate to KT in Aboriginal/Torres Strait Islander research, regardless of the research topic. Results will be used to inform the KT definition, method and practices that can be used in Aboriginal/Torres Strait Islander research contexts in Australia. Ethics and dissemination: The Mayi Kuwayu Study has ethics approvals from the Australian Institute of Aboriginal and Torres Strait Islander Studies, 12 Aboriginal/Torres Strait Islander organisations, and the Australian National University Human Research Ethics Committee. Results will be disseminated through peer-review publication and community workshops. Protocol registration is available online (10.17605/OSF.IO/JMFQ3).